Alterations of the anterior lens capsule associated with climatic keratopathy. Issue 3 (March 1989) - Johnson, G; Minassian, D; Franken, S
Abstract : We describe changes in the anterior lens capsules of older people in Somalia, a country which is close to the equator and with large areas of sand, often highly reflective of sunlight. The capsule changes are confined to the central pupillary area. In order of apparently increasing severity they consist of a white opalescence ('frosting'), an elevation in front of the contour of the rest of the lens to form a plateau, and a 'bag' or herniation of the lens capsule through the pupil. Plateau and bagging taken together are strongly associated with climatic keratopathy (and by inference with reflected ultraviolet exposure), weakly associated with exfoliation syndrome, inversely related to the degree of cataract, and interfere severely with vision.